Fate of petroleum-based and plant-based teabags exposed to environmental soil conditions for one year - Mateos–Cárdenas, Alicia (Frontiers in Bioengineering and Biotechnology, 2022)
Petroleum-based plastics are materials which have provided important industrial benefits from being lightweight and having low production costs. However, plastic pollution is pervasive and ubiquitous on all environments. This has led some industries to rapidly introduce the so called ‘bioplastics’ into the market by switching the conventional ones for new plant-based alternatives with similar properties. However, little is known about the fate of such alternatives especially in the open environment. In this novel study, the degradation of teabags from eight different brands was investigated, five petroleum based (cellulose-PP blend) and three plant-based (cellulose, cellulose-PLA blend and PLA). The degradation was tested under real-environmental soil conditions over a 12-month period. Fourier Transform Infrared Spectroscopy (FTIR-ATR) and Scanning Electron Microscopy (SEM) techniques were used to examine the change in polymer makeup and surface degradation of teabags at 3 weeks, 3.5, 6 and 12 months. Teabag dry weight and any retrieved fragments were measured over time. Teabags that contained a plastic blended to cellulose were brittle or degraded into smaller fragments after 3 weeks in soil. Parallel to this, the cellulose layer also degraded in this short timeline. Petroleum-based teabags produced the highest numbers of PP fragments overtime and fragmented teabags were still found after 12 months. Plant-based teabags made of cellulose only or a blend of cellulose-PLA were absent from soil samples after 3.5 months, including no fragments. Contrary to this, teabags made of PLA which were marketed as completely biodegradable, persisted completely intact in soil throughout all time points. The novel results from this study provide a perspective on plastic degradation in terrestrial sources. Based on these findings, it can be recommended that teabags mostly made of cellulose or cellulose blended with a bioplastic present in a smaller ratio, are a better alternative to petroleum-based or pure PLA plastics, in terms of rapid environmental degradation. Further studies should focus on their ecotoxicity, additive presence, microbial degradation and life cycle in order to draw a full environmental assessment.